Meta-analysis Study of Work-related Musculoskeletal Disorders in Iran - Ayoub Parno; Kourosh Sayehmiri; Reza Nabi Amjad; Reyhaneh Ivanbagha; Mir Mohammad Hosseini Ahagh; Shiva Hosseini Foladi; Alireza Khammar; Mohsen Poursadeqiyan (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: Work-related musculoskeletal disorders are one of the major causes of lost working time, increased costs, human injuries and burnout. The International Labor Organization estimates that about 160 million work-related illnesses occur worldwide each year, where the highest prevalent illnesses are musculoskeletal disorders. Several studies have been conducted In Iran to investigate the prevalence of these disorders, each providing different statistics. Therefore, considering the importance of these disorders, it is necessary to obtain accurate results with high statistical power and validate them. The aim of this study was to investigate the prevalence of work-related musculoskeletal disorders in Iran in order to obtain more accurate results by conducting a meta-analysis. Materials & Methods: For this meta-analysis, searching was conducted in SID, MagIran, IranMedex, Google Scholar, Scopus, Web of Science, and PubMed databases using the keyword "work-related musculoskeletal disorders" in both Persian and English on studies conducted during 2001-2016 in various cities of Iran. Inclusion criteria were: investigating the prevalence of musculoskeletal disorders in a period of one year, being a cross-sectional or descriptive-analytical study, publication in Persian or English, availability of full-texts, assessment using standard methods (e.g. Nordic Musculoskeletal Questionnaire) and considering the prevalence of musculoskeletal disorders throughout the body (upper and lower extremities). The heterogeneity of the articles was evaluated using the I2 statistics and the data were analyzed in STATA software using meta-analysis and random-effects model. Results: In this study, 45 papers on work-related musculoskeletal disorders were studied. The overall sample size of these studies was 9813, with a mean number of 218 for each study. Most of studies were descriptive-analytical and cross-sectional. In all of them, the prevalence of musculoskeletal disorders in different parts of the body had been investigated. According to their results, the most prevalent work-related musculoskeletal disorder in lower extremity was low back pain (0.49%) and in upper extremity, it was neck pain (39.3%). The prevalence of musculoskeletal disorders in other parts of the body were 39.32% in the neck, 36.9% in shoulders, 36.8% in the back, 34% in the wrist, 26.9% in legs, 20.5% in thighs and hips, and 16.2% in elbows.